Analysis of the Determining Factors of Generation Z's Interest in Working in the Agricultural Sector in Bima Regency - Awaludin, Muhammad; Maryam, ST; Fadliyanti, Luluk (Jurnal Social Economic of Agriculture, 2024)
This research is motivated by the phenomenon of the high interest of generation Z in Bima Regency in choosing to work in the agricultural sector. This research aims to analyze the influence of various factors, such as family economic conditions, environment, personality, motivation, and farming experience, on Generation Z's interest in choosing to work in the agricultural sector in the Bima Regency area. The type of research used is quantitative-descriptive. The population is generation Z, aged 15"“24 years, who work as farmers or in the agricultural sector in six sub-districts in Bima Regency, namely Lambu, Monta, Wera, Langgudu, Belo, and Sape, with a total sample of 322 respondents. Primary data collection was carried out through interviews, observation, and documentation using questionnaire instruments and Google Forms. The data analysis was carried out using the multiple linear regression method. The results of the analysis show that partially family economic factors, environment, personality, motivation, and farming experience have a positive and significant effect on generation Z's interest in working in the agricultural sector in Bima Regency. Meanwhile, simultaneously, family economic variables, environment, personality, motivation, and farming experience have a positive and significant effect on generation Z's interest in working in the agricultural sector in Bima Regency.